Agricultural development and international trade - Anderson, Kym; Martin, Will (International Food Policy Research Institute, 2021)
Traditionally societies and their governments have pursued agricultural development to ensure adequate food is available and affordable and incomes of farm households keep pace with those of nonfarm households. Today the farm sector is also expected to care for the natural environment, ensure the food it supplies is safe and nutritious, contribute to energy security, help reduce poverty and greenhouse gas emissions, and provide employment and investment opportunities for women as much as for men. Farm productivity growth can contribute to many of these goals and can be accelerated through more targeted investments in applied agricultural research and in rural infrastructure, education, and health. However, each society does not have to achieve these and their other goals in isolation and indeed will be less able to as climate changes add to the volatility of domestic production. Fortunately, each country’s evolving consumption preferences and the wherewithal to satisfy them can be enhanced through trading more openly with other societies. This chapter shows how. It explains the contributions international trade openness can make—and has made—toward achieving these goals. In doing so, the chapter clarifies the role agricultural trade can play, in contrast to trying to remain self-sufficient in food. We draw out the implications for agricultural development prospects in various types of countries as the world economy grows.